The Effect of Price Perception, Consumer Income, and Consumer Preferences on the Demand for Tourism Services (Case Study at Sea World Ancol) - Oktavia, Rika; Nikensari, Sri Indah; Iranto, Dicky (The Future of Education Journal, 2025)
This study aims to determine the effect of price perception, consumer income, and consumer preferences on the demand for tourism services in the case study of Sea World Ancol. This research is quantitative in nature. The data source in this study uses primary data. Data collection was carried out using purposive sampling with criteria including visitors who have visited or are currently visiting Sea World Ancol, with the visitors being domestic tourists. The research sample consists of 200 respondents. This study uses Multiple Linear Regression analysis. The results of this study show that: 1) Price perception has a positive and significant effect on the demand for tourism services, 2) Consumer income has a positive and significant effect on the demand for tourism services, 3) Consumer preferences have a positive and significant effect on the demand for tourism services, and 4) Price perception, consumer income, and consumer preferences simultaneously have a significant effect on the demand for tourism services in the case study of Sea World Ancol.